Korelasi ukuran tubuh dengan bobot karkas sapi Madura di Pamekasan - Zulfaini Shamad; Cepryana Sathalica Widyananda; Veronica Margareta Ani Nurgiartiningsih (Jurnal Ilmu Peternakan Terapan, 2023)
Madura cattle are one of the genetic resources in Indonesia that need to be preserved. The purpose of this study was to determine the relationship between body measurement and carcass weight in Madura cattle, making it easier to determine carcass weight by only measuring body mesurement. This research was conducted in a slaughter house Pamekasan Regency. The material used in this study were 307 Madura cattle aged 1.5–4 years (P1, P2, P3). The results indicated that the number of slaughtering male Madura cattle was 232 tails (75.52%) more than the female slaughter was 75 tails (24.44%). The results of the correlation coefficient analysis of body measurement with carcass weight of Madura cattle P1, P2 and P3 showed that there was a very significant relationship between body mesurement and carcass weight (P<0.01), with the correlation value between body length, body height and chest girth with carcass weight in cattle. Madura respectively were 0.63, 0.38 and 0.78 at the age of P1, 0.54, 0.55 and 0.84 at the age of P2, 0.32, 0.14 and 0.78 at the age of P3. The highest correlation coefficient values were found between chest girth with carcass weight, respectively (0.76 , 0.84 and 0.78 for P1, P2 and PI 3). The conclusion that based on the highest correlation value between chest girth with carcass weight, chest girth can be used to estimate carcass weight.